MASS-MEDIA AS A CONSTITUENT OF HUMAN COMMUNICATION - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article investigates the role of the mass-media in the system of human communication depending on its social scale.